First accelerator mass spectrometry I4C dates documenting contemporaneity of nonanalog species in late Pleistocene mammal communities - Stafford, T.W.; Semken, H.A.; Graham, R.W.; Klippe, W.F.; Markova, A.; Smirnov, N.G.; Southon, J. (My University, 1999)
Worldwide late Pleistocene terrestrial mammal faunas are characterized by stratigraphic associaiicns of species that now have exclusive geographic ranges. These have been interpreted as either taphonomically mixed or representative of communities that no longer exist. Accelerator mass spectrometry 14C dates (n = 60) on single bones of stratigraphically associated fossil micromammals from two American and two Russian sites document for the first time that currently allopatric mammals occurred together between 12,000 and 22,000 yr B.P. on two continents. The existence of mammal communities without modem analogs demonstrates that Northern Hemisphere biological communities are ephemeral and that many modern biomes are younger than 12 ka. Future climate change may result in new nonanalog communities.
Keywords: Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен